Q: Factor 2x2 plus 3x - 14?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

(x + 1) / (2x3 + 3x + 5) --- Can't depict long division here, but you can work this out by seeing if (x + 1) is a factor of (2x3 + 3x + 5). If it is, then the answer will be 1/(the other factor). In this case, that is true. (2x3 + 3x + 5)/(x + 1) = 2x2 - 2x + 5, so the term term above is equal to: 1 / (2x2 - 2x + 5)

2x2 + 7x + 6 = 2x2 + 4x + 3x + 6 = 2x(x + 2) + 3(x + 2) = (x + 2)(2x + 3)

You can easily factor this:2x2 + 3x = 0x(2x + 3) = 0Separate this into two equations, one for each solution:x = 02x + 3 = 02x = -3x = -3/2So the two solutions are 0, and -3/2.You can easily factor this:2x2 + 3x = 0x(2x + 3) = 0Separate this into two equations, one for each solution:x = 02x + 3 = 02x = -3x = -3/2So the two solutions are 0, and -3/2.You can easily factor this:2x2 + 3x = 0x(2x + 3) = 0Separate this into two equations, one for each solution:x = 02x + 3 = 02x = -3x = -3/2So the two solutions are 0, and -3/2.You can easily factor this:2x2 + 3x = 0x(2x + 3) = 0Separate this into two equations, one for each solution:x = 02x + 3 = 02x = -3x = -3/2So the two solutions are 0, and -3/2.

2x3 + 8x2 + 3x + 12 = (2x3 + 8x2) + (3x + 12) = 2x2(x + 4) + 3(x + 4) = (x + 4)(2x2 + 3) Since you have asked this question I am assuming that you are not yet at a level where you might want (2x2 + 3) factorised into its imaginary factors.

4x3+12x2+3x+9

Related questions

(2x + 7)(x - 2)

No. You'd have to use the ABC-formula

2x2-4x-3x+6 2x2-7x+6 (2x+3)(x+2)

(2x + 7)(x - 2)

(3x - 1)(2x2 - 2x - 1)

(2x + 7)(x - 2)

2x2 + 3x + 1 = (x + 1)(2x + 1)

d/dx 2x2+3x+7=4x+3

x3 + 2x2 + 3x + 6 = x2(x + 2) + 3(x + 2) = (x + 2)(x2 + 3)

2x2 equals 5

2x2-3x-5 = (2x-5)(x+1) when factored

-11